Determinants of antibiotic prescription in paediatric patients: The case of two hospitals in Maputo, Mozambique - L G S Monteiro; A Chauque; M P Barros; T R Ira (South African Medical Association, 2017)
Background. The need for healthcare in paediatric patients is often due to respiratory diseases, acute diarrhoea and viral fever, which suggests a limited need for the use of antibiotics. Objectives. To identify the determinants of antibiotic prescription in hospitalised paediatric patients in Mozambique. Methods. A cross-sectional study was conducted between January and June 2015. A total of 454 medical prescriptions and clinical records of children aged 0 - 14 years from Hospital Central de Maputo (HCM) and Hospital Geral de Mavalane (HGM) were analysed. Results. Antibiotics were used in 97.6% of the patients, with no significant differences (p>0.05) in the prescription rates of the hospitals. The most commonly used antibiotics were beta-lactams (57.3%), aminoglycosides (28.3%) and co-trimoxazole (9.4%). Antibiotics were prescribed in all cases of bronchopneumonia, fever, sepsis and acute gastroenteritis. For malaria and undefined diagnoses, antibiotics were prescribed 97.8% and 99.3% of cases, respectively. It was clear that most severe clinical conditions (odds ratio (OR) 9.06; 1.13 - 12.14) and age <5 years (OR 5.47;1.54 - 7.60) were treated with antibiotics. Conclusion. The prescription of antibiotics for paediatric patients at both HCM and HGM was largely influenced by patients' clinical condition and age. It showed that physicians used an empirical approach, in the absence of laboratory tests, often leading to unnecessary antibiotic treatments with negative causative effects. Physicians should be encouraged to use an evidence-based approach for managing the cases correctly.